The Serotonergic Raphe Promote Sleep in Zebrafish and Mice - Oikonomou, Grigorios; Altermatt, Michael; Zhang, Rong-wei; Coughlin, Gerard M.; Montz, Christin; Gradinaru, Viviana; Prober, David A. (Neuron (Cambridge, Mass.), 2019)
The role of serotonin (5-HT) in sleep is controversial: early studies suggested a sleep-promoting role, but eventually the paradigm shifted toward a wake-promoting function for the serotonergic raphe. Here, we provide evidence from zebrafish and mice that the raphe are critical for the initiation and maintenance of sleep. In zebrafish, genetic ablation of 5-HT production by the raphe reduces sleep, sleep depth, and the homeostatic response to sleep deprivation. Pharmacological inhibition or ablation of the raphe reduces sleep, while optogenetic stimulation increases sleep. Similarly, in mice, ablation of the raphe increases wakefulness and impairs the homeostatic response to sleep deprivation, whereas tonic optogenetic stimulation at a rate similar to baseline activity induces sleep. Interestingly, burst optogenetic stimulation induces wakefulness in accordance with previously described burst activity of the raphe during arousing stimuli. These results indicate that the serotonergic system promotes sleep in both diurnal zebrafish and nocturnal rodents. [Display omitted] •The serotonergic system (STS) promotes sleep in zebrafish and mice•STS disruption reduces both sleep and the homeostatic response to sleep deprivation•Tonic stimulation of the STS induces sleep, but burst stimulation induces wake•We propose that baseline tonic STS activity during wake generates sleep pressure The wake-active serotonergic system (STS) has been considered part of the ascending arousal system that promotes wakefulness. Using zebrafish and mice, Oikonomou, Altermatt et al. demonstrate that the STS promotes sleep, potentially by generating homeostatic sleep pressure during wakefulness.